STRATEGY OF COMMUNITY RADIO JANGKAR KELUD IN THE DEVELOPMENT OF NETWORK FRIENDSHIP COMMUNITY - Anam Miftakhul Huda (Universitas Islam Balitar, 2019)
This study examines the importance of the existence of community radio in disaster-prone areas, specifically in the field of disaster information and disaster mitigation for the surrounding community, the existence of community radio is very important as a means of various information and the adhesive of brotherhood in society. Jangkar Kelud community radio is a mass media engaged in broadcasts in the Kelud Ring area, namely in Blitar Regency, Malang Regency and Kediri Regency. This Radio was formed by a group of people in the Kelud Circle. The benefits of community radio are not when a disaster occurs, but the benefits of radio as a disaster mitigation media are very important continuously to convey awareness to the community. This type of research is descriptive qualitative, by adopting observations, interviews and documentation. The research methodw used is a qualitative method, because the method used is the result of interviews with informants as the primary data obtained from observations on the location of research on the data from the informant. The results of this study are, the strategy of building intimacy between the residents and the Jangkar Kelud community through the gathering, sinau together, social gathering, groups on Social media. Where the distribution is not seen by people at different levels, all have the same position and optimize the community within the Kelud Ring.